The healing effect of bone marrow-derived stem cells and aquatic activity in Achilles tendon injury - SHEIKHANI-SHAHIN, H.; MEHRABANI, D.; ASHRAF, M. J.; RAJABI, H.; NOROUZIAN, M.; RAHMANIFAR, F.; DEHGHANI NAZHVANI, S.; ZARE, S. (Journal of the Hellenic Veterinary Medical Society, 2019)
The common treatment recommended for Achilles tendon rupture as the most common tendon injury during exercise is surgical intervention, while it eventually causes various clinical problems. This study assessed the healing effect of bone marrow-derived stem cells (BMSCs) and aquatic activities in Achilles tendon injury. Forty rats were randomly divided into 5 equal groups. Group 1 underwent aquatic activity, 72 h after a crush lesion formed on Achilles tendon, group 2 received 1×106 intra-articular BMSCs post-tendon injury, group 3 had aquatic activity together with BMSCs transplantation after tendon damage, group 4 just experienced tendon injury without any treatment intervention and group 5 was considered as the control group while did not undergo any tendon injury and did not receive any treatment measure. After 8 weeks, the animals were sacrificed and the tendons were transferred in 10% formalin for histological evaluation. There was a significant increase in fibroblast number in group 3 in comparison to other groups. However, there was a significant increase in collagen deposition in groups 2, 3 and 5 in comparison to group 1 and 4. A significant decrease was noted for cellularity in group 2 when compared to groups 1 and 4. Regarding tendon diameter in group 3; a significant healing was observed when compared to groups 2, 4 and 5. It was shown that aquatic activity together with cell transplantation was an effective therapeutic measure enhancing the healing in tendon injuries. These findings can open a window in sport medicine in treatment of tendon injuries.